Struggling or Succeeding in Science and Technology Education: Elementary School Students’ Individual Differences During Inquiry- and Design-Based Learning - Slim, Tessa; van Schaik, Johanna E.; Dobber, Marjolein; Hotze, Anna C. G.; Raijmakers, Maartje E. J. (Frontiers in Education, 2022)
The primary aim of this study was to identify how students’ individual differences are related to their learning outcomes and learning process in science and technology (S&T) education, using a mixed methods design. At the start of the study, we assessed the reading comprehension, math skills, science skills, executive functions, coherence of speech, science curiosity and attitude towards S&T of 73 fifth and sixth graders. The students then received a four-lesson inquiry- and design-based learning unit on the concept of sound. Learning outcomes were measured through a pre- and post-test regarding students’ conceptual knowledge of sound, a practical assessment of design skills and a situational interest measure. A factor score regression model (N = 62) showed significant influence from prior conceptual knowledge and the latent factor “academic abilities” (reading, math and science skills) on post conceptual knowledge. The latent factor “affective” (curiosity and attitude towards S&T) and to a lesser extend also prior conceptual knowledge were predictive of situational interest. Learning process was measured through individual interviews and student worksheets within a subsample (N = 24). We used latent profile analysis to identify three profiles based on students’ individual differences, from which the subsample for qualitative analyses was selected. Codes and themes that emerged from the qualitative analyses revealed differences between students from the three profiles. The results of this study show how different types of students succeed or struggle within S&T education, which is essential for teachers in order to differentiate their instruction and guidance. Differentiation aimed at supporting language and the integration of science into design, while facilitating a variety of learning activities and assessments that move beyond written assignments, could help achieve the most optimal learning conditions for each student.